The Influence of Work Motivation and Work Discipline on the Performance of Elementary School Teachers in Clusters 1 and 2 in Onan Ganjang District, Humbang Hasundutan Regency - Hutasoit, Rolambok; Marbun, Rencan Carisma; Panjaitan, Binur; Samosir, Lustani; Saragih, Ratna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of Work Motivation and Work Discipline on Performance partially or simultaneously, with the hypothesis that there is a positive effect of Work Motivation and Work Discipline on the Performance of Elementary School Teachers in Cluster 1 and 2 in Onan Ganjang District, Humbang Hasundutan Regency, both partially and simultaneously. This study uses a descriptive quantitative method. The population of the study was all teachers of Elementary Schools in Cluster 1 and 2 in Onan Ganjang District, totaling 63 people with a sample of 63 people. The research instrument was a closed questionnaire, which was compiled by the researcher based on the research variable indicators. The questionnaire trial was conducted on 30 teachers outside the research sample, and has been tested with validity and reliability tests. The data analysis technique was with multiple linear regression tests. The results of this study recommend to teachers that in order to improve teacher performance, Work Motivation and Work Discipline must continue to be improved.